2019
DOI: 10.2337/dc19-0100
|View full text |Cite
|
Sign up to set email alerts
|

High-Coverage Targeted Lipidomics Reveals Novel Serum Lipid Predictors and Lipid Pathway Dysregulation Antecedent to Type 2 Diabetes Onset in Normoglycemic Chinese Adults

Abstract: Comprehensive assessment of serum lipidomic aberrations before type 2 diabetes mellitus (T2DM) onset has remained lacking in Han Chinese. We evaluated changes in lipid coregulation antecedent to T2DM and identified novel lipid predictors for T2DM in individuals with normal glucose regulation (NGR). RESEARCH DESIGN AND METHODSIn the discovery study, we tested 667 baseline serum lipids in subjects with incident diabetes and propensity score-matched control subjects (n = 200) from a prospective cohort comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 33 publications
8
96
1
Order By: Relevance
“…Of note, 1deoxysphingolipids have also been found to be elevated in individuals with type 2 diabetes and in non-diabetic individuals with the metabolic syndrome [28]. Moreover, 1-deoxysphingolipid levels were also increased in individuals with type 2 diabetes who had polyneuropathy, when compared with healthy individuals, but there were no correlations between these levels and peripheral nerve function tests or the clinical neuropathy stages [12]. In an open-label clinical trial in individuals with primary hypercholesterolemia or mixed dyslipidaemia, treatment with fenofibrate for 6 weeks resulted in lowering of plasma 1deoxysphingolipid levels [29].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of note, 1deoxysphingolipids have also been found to be elevated in individuals with type 2 diabetes and in non-diabetic individuals with the metabolic syndrome [28]. Moreover, 1-deoxysphingolipid levels were also increased in individuals with type 2 diabetes who had polyneuropathy, when compared with healthy individuals, but there were no correlations between these levels and peripheral nerve function tests or the clinical neuropathy stages [12]. In an open-label clinical trial in individuals with primary hypercholesterolemia or mixed dyslipidaemia, treatment with fenofibrate for 6 weeks resulted in lowering of plasma 1deoxysphingolipid levels [29].…”
Section: Discussionmentioning
confidence: 96%
“…Higher concentrations of specific SMs have recently been found to predict incident type 2 diabetes in prospective sphingolipidomics studies over 6 and 11 years, respectively [26,27]. The formation of atypical neurotoxic deoxysphingolipids has been identified to play a causative role in the development of hereditary sensory and autonomic neuropathy type 1 (HSAN1) [12]. Of note, 1deoxysphingolipids have also been found to be elevated in individuals with type 2 diabetes and in non-diabetic individuals with the metabolic syndrome [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipids were analyzed by liquid chromatography/mass spectrometry. In brief, phospholipids were separated on a Phenomenex Luna Silica 3-µm column (internal diameter 150 × 2.0 mm; Lu et al, 2019 ). Individual polar lipid species were quantified by referencing to spiked internal standards including PtdCho (14:0/14:0), PtdEtn (14:0/14:0), d31-PtdSer (16:0/18:1), PtdSer (17:0/20:4), PtdOH (17:0/17:0), PtdOH (17:0/20:4), and phosphatidylglycerol (14:0/14:0) obtained from Avanti Polar Lipids.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to BCAAs, the composition of the lipidome has been shown to differ according to glycemic status [8], and phospholipids such as lysophosphatidylcholines (LPCs) have been demonstrated to be associated with obesity and diabetes [9]. In a study in the Chinese population, lipids, including triacylglycerols, lyso-phosphatidylinositols, phosphatidylcholines, polyunsaturated fatty acid-plasmalogen phosphatidylethanolamines, and cholesteryl esters, were shown to be related to the future development of type 2 diabetes [10]. Moreover, it has been suggested that LPCs may mediate the metabolic effects of metformin [11,12].…”
Section: Introductionmentioning
confidence: 99%